The impact of cross-border movement on South African towns on the Lesotho border - Johan Viljoen; Marie Wentzel (Acta Academica, 2007)
This article investigates the impact of cross-border movement from Lesotho to the eastern Free State towns of Ficksburg, Ladybrand and Wepener. The many Basotho who visit these towns have a tangible impact on economic activity and service provision. The findings include, among other things, the major economic benefits for the border towns and the impact on South Africa’s health and education services. Stakeholders attributed both the fast growth of informal settlements and the high rate of unemployment to the movement of Lesotho citizens, but this could not be verified. Policy recommendations include the need to facilitate the flow of people and to garner reliable information on which to base planning and decision-making.